Pematahan dormansi benih cabai lokal tiung tanjung asal tabalong Kalimantan Selatan - Hasimi, Muhammad Hasbi; Agustina, Eva; Miskiah, Nur Yohaniz; Fadhiel, Muhammad Ihsan; Nadia, Nadia; Jawak, Gani (Jurnal AGRO, 2024)
Tiung Tanjung seeds pepper are believed to have dormant properties that can be detrimental to farmers during planting. The aim of this study was to find out the correct method of breaking the dormancy on Tiung Tanjung pepper. The study was designed with a two-stage nested design, the first stage was the seed storage time of 1, 3, 5, 7, 9, and 11 weeks. The second stage was a dormant breakdown method consisting of 8 treatments namely control, aquades, warm water (40 °C), ionic water, IAA 100 ppm, IAA 200 ppm, KNO3 0,1% and KNO3 0.5%. Each unit of experiment used 3 repetitions with 25 seeds planted using Top of Paper method (TP). Parameters observed were the vigor index, growth speed, germination,maximum germination potential, fresh seed, seed mortality rate, and growth performance. The results of the study showed that the treatment of Tiung pepper seed immersed in 0.5% KNO3 for 24 hours was able to break the dormancy at 7 weeks after storage with germination values increased to 80%. Treatment with 0.1% KNO3 could break the dormancy in the 9th week. Dormancy breakdown treatments with aquades, warm water (40 °C), ionic water, IAA 100 ppm, and IAA 200 ppm had not been able to break the dormancy of Tiung pepper seeds up to 11 weeks of storage. Benih cabai Tiung Tanjung diyakini memiliki sifat dormansi yang dapat merugikan petani saat penanaman. Tujuan dari penelitian ini adalah untuk mengetahui metode pematahan dormansi yang tepat pada cabai Tiung Tanjung. Penelitian dilaksanakan dengan rancangan tersarang dua tingkat, tingkat pertama adalah lama masa simpan benih yaitu 1, 3, 5, 7, 9, dan 11 minggu simpan dan tingkat kedua adalah metode pematahan dormansi yang terdiri dari 8 perlakuan yaitu kontrol, akuades, air hangat (40 °C), air ion, IAA 100 ppm, IAA 200 ppm, KNO3 0,1% dan KNO3 0,5%. Setiap satuan percobaan menggunakan 3 ulangan. Setiap ulangan menggunakan 25 benih yang ditanam dengan metode uji di atas kertas (UDK). Parameter yang diamati adalah indeks vigor, kecepatan tumbuh, daya berkecambah, potensi tumbuh maksimum, benih segar tidak tumbuh, dan tingkat kematian benih, dan performa kecambah. Hasil penelitian menunjukkan bahwa perlakuan perendaman benih cabai Tiung dalam KNO3 0,5% selama 24 jam mampu mematahkan dormansi pada 7 minggu setelah simpan dengan nilai daya berkecambah mencapai 80%. Perlakuan dengan KNO3 0,1% dapat mematahkan dormansi pada minggu ke-9. Perlakuan pematahan dormansi dengan akuades, air hangat (40 °C), air ion, IAA 100 ppm dan IAA 200 ppm belum mampu mematahkan dormansi benih cabai Tiung hingga 11 minggu simpan.